2014
DOI: 10.3389/fpsyg.2014.00657
|View full text |Cite
|
Sign up to set email alerts
|

How important is importance for prospective memory? A review

Abstract: Forgetting to carry out an intention as planned can have serious consequences in everyday life. People sometimes even forget intentions that they consider as very important. Here, we review the literature on the impact of importance on prospective memory performance. We highlight different methods used to manipulate the importance of a prospective memory task such as providing rewards, importance relative to other ongoing activities, absolute importance, and providing social motives. Moreover, we address the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 62 publications
3
78
0
1
Order By: Relevance
“…McDaniel & Einstein, 2000). Important intentions are remembered better, however, at least in laboratory studies this performance enhancement is typically associated with a performance cost in the ongoing task in which the prospective memory task is embedded (see Walter & Meier, 2014 for a recent review). Importance can be varied by emphasizing the prospective memory task relative to the ongoing task (relative importance), by emphasizing the prospective memory task per se (absolute importance), by providing a reward or by providing a social motive (social importance) to perform the prospective memory task.…”
mentioning
confidence: 99%
“…McDaniel & Einstein, 2000). Important intentions are remembered better, however, at least in laboratory studies this performance enhancement is typically associated with a performance cost in the ongoing task in which the prospective memory task is embedded (see Walter & Meier, 2014 for a recent review). Importance can be varied by emphasizing the prospective memory task relative to the ongoing task (relative importance), by emphasizing the prospective memory task per se (absolute importance), by providing a reward or by providing a social motive (social importance) to perform the prospective memory task.…”
mentioning
confidence: 99%
“…The observation that overall cue detection further increased across experiments in the wake groups could be explained by the increasing number of intention instructions and execution of the task. Previous evidence indicates that the perceived importance of the prospective memory task affects cue detection performance, with higher importance typically leading to better cue detection (McDaniel and Einstein, 2000; Walter and Meier, 2014, 2016). Considering that in the present study, additional (re-)instructions were introduced in each of the successive experiments, this might have inadvertently added further importance to the prospective memory task, increasing relevance in the intentional memory network.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, the present study shows that absolute importance improves ProM performance at no costs (cf. Meier & Rey‐Mermet, ; Scullin, McDaniel, & Einstein, ; Walter & Meier, ). We suggest that absolute importance may induce similar mechanisms as some metacognitive strategies (cf.…”
Section: Discussionmentioning
confidence: 99%
“…So far, task importance was mainly manipulated by emphasizing the importance of the ProM task relative to the ongoing task or vice versa (i.e., relative importance manipulation; cf. Kliegel, Martin, McDaniel, & Einstein, ; Walter & Meier, ). The results have shown that ProM performance can be increased by the manipulation of task importance, at least when the overlap of processing requirements was low.…”
mentioning
confidence: 99%